The Effect of Assocıate Degree Students' Cognıtıve Behavıoral Physıcal Actıvıty Levels on the Enjoyment of Physıcal Actıvıtıes - Gökhan Dokuzoğlu; Çağatay Dereceli; Ebru Dereceli (Atatürk University, 2024)
This study was conducted to examine the impact of cognitive-behavioral physical activity levels on enjoyment of physical activities among associate degree students. The study involved students enrolled in the Health Services Vocational School of a state university in the Aegean region. Participants were provided with digital survey forms, and 414 survey forms were evaluated. The first section of the study consisted of a personal information form, the second section included the "Cognitive Behavioral Physical Activity Scale (CBPAS)," adapted into Turkish by Eskiler et al. (2016) from the scale developed by Schembre et al. (2015), and the third section utilized the "Physical Activity Enjoyment Scale" adapted into Turkish by Özkurt et al. (2022) from the scale developed by Mullen et al. (2011). Significant differences were found between participants' gender, income status, and place of residence variables and their cognitive-behavioral physical activity levels. Furthermore, statistically significant differences were observed in the outcome expectation dimension and total score of cognitive-behavioral physical activity based on the place of residence variable. Significant differences were also noted between the enjoyment levels of physical activity and the place of residence. Additionally, statistically significant differences were detected in all variables between regular sports participation status and cognitive-behavioral physical activity levels, as well as enjoyment levels of physical activity. In conclusion, it was determined that participants' cognitive-behavioral physical activity levels had a significant and positive effect on their enjoyment levels of physical activities.